FEATURES OF MODERN SCIENCE - Usmonov Murod Sodiqovich (Galaxy International Interdisciplinary Research Journal, 2022)
The responsibility of continuing the achievements gained due to independence, thinking about the intellectual potential of the country, successfully moving forward along the path of comprehensive development of society, strengthening its independence falls on the masses of today’s creative (researchers). Therefore, the use of new machines, machines, methodologies, algorithms, models, computers, etc., created on the basis of the achievements of Science and Technology, Automatic control of their preparation and introduction into practice, requires great scientific training from people.